Germination variety Test Two Plantcane (Saccharum Officinarum L.) The Use of Breeding Mule Shoots With Different Eyes Lay - Yeni Ika Pratiwi; Fauziatun Nisak; Bambang Wicaksono Hariyadi; Nurul Huda (Faculty of Agriculture, Merdeka University Surabaya, 2019)
The number of clumps per hectare is influenced by the percentage of germination of kinds of seeds used (Tamelsilva, 2006). Increasing the production of sugar cane as a raw material for sugar is absolutely necessary. One of the causes of the decline in sugarcane productivity is the problem in the use of seeds, such as sugarcane seeds used by farmers who are less qualified (Iskandar, 2005). The study was conducted at the Experimental Garden of the Faculty of Agriculture, Merdeka University, Surabaya, in March-April 2017. Using a Randomized Block Design (RBD) consisting of six treatment combinations with three replications and two sample plants. As for the combination treatment, as follows: A (Variety LPS-864 and Buds Buds section 20); B (Variant LPS-864 and Mata Tunas Middle-segment-14); C (Variety of LPS-864 and Mata Tunas at the base of Section-08); D (Variety of LPS-891 and Buds section of Section-20); E (Variant LPS-891 and Mata Tunas Middle-segment-14); F (Variety of LPS-891 and Mata Tunas at the base of segment-08). The results showed that the treatment of the combination of the location of the buds and varieties significantly affected the observation of the number of leaves, but the effect was very significant on the variable of germination speed and length of the plant and the wet weight of the plant. Combination treatment of bud location on segment-20 (shoots) on the sugar cane varieties LPS-891 and cane varieties LPS-864 showed the best results on all observational variables, although the highest results always indicated the location of bud-section 20 buds (shoots) on sugarcane varieties LPS-891, but statistically not significantly different.